The Expectations of Employers in the E-Commerce Industry Related to the Competencies of University Graduates - Małgorzata TYRAŃSKA; Angelika WODECKA-HYJEK; Mariusz ŁAPCZYŃSKI; Bernard ZIĘBICKI (Communications of International Proceedings, 2021)
The article presents research findings concerning the expectations of employers in the e-commerce industry regarding the competences of university graduates. The first part of the study, based on a literature review and research reports, presents the development of the e-commerce industry worldwide, and the models of the competences required in the digital economy. The empirical study, the results of which are presented in the second part of the paper, consisted in analyzing the content of job announcements related to the e-commerce industry in Poland in 2020. Job announcements addressed directly to university graduates, posted on the praca.pl website, popular in Poland, were analyzed. For that purpose, computer tools for analyzing qualitative data were used (large sets of text data). As a result of the studies performed, a set of tasks (duties) and competences at the work positions related to the job announcements was identified. The results obtained in this way were subjected to an aggregation analysis in order to determine the key categories of the professional competences expected, related to the e-commerce industry. In the summary, the offers identified in the global literature were compared with the results of the empirical studies, and determinants were indicated for the contemporary labor market in the e-commerce industry.
Keywords: e-commerce; individual competences; higher education